Influence of ozonized water on pain, oedema, and trismus during impacted third molar surgery: a randomized, triple blind clinical trial - José Cristiano Ramos Glória; Dhelfeson Willya Douglas-; Larissa Doalla Almeida e Silva; Saulo Gabriel Moreira Falci; Cássio Roberto Rocha dos Santos (BMC, 2020)
Abstract Background This study aimed to evaluate the efficacy of ozonized water on pain, oedema and trismus after impacted third molar mandibular surgeries when compared to double distilled water. A randomized triple blind trial was conducted. Methods Patients with third molars class II-B of Pell-Gregory were included, and surgical extraction was performed. Irrigation was done with ozonized (group 1) or double distilled water (group 2). The type of irrigation and the side to be operated were randomized. Neither the patients nor the operator or evaluator were aware of the irrigation solution. Pain, oedema and trismus were evaluated at baseline, 24-h, 48-h, 72-h and 7-days after treatment. The data were evaluated by Friedman, Wilcoxon, Mann-Whitney tests, and size effect. Results It was included 8 men and 12 women, with a mean age of 20.9y.o. The initial pain mean was 7.94 (±12.81) (group 1) and 5.50 (±9.12) (group 2) (p > 0,05). There was a statistically significant reduction of pain, oedema and trismus in intragroup analysis (p < 0.05). There was no statistically significant difference (p > 0.05) when comparing the oedema and trismus between groups. The size effect ranged from small (0.23) to large (1.29). Conclusions It was concluded that ozonized water was compatible as irrigation method, not inferior to double distilled water, and had satisfactory effects on management of pain, oedema and trismus after surgical removal of the third molar. Trial registration This clinical trial was registered in ClinicalTrials.gov NCT03501225 on April 18, 2018.